Tax strategies drive earnings management in Indonesia: Strategi pajak mendorong manajemen laba di Indonesia - Alfadin, Muhamad Fahmi; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the direct and indirect effects of tax planning and deferred tax expense on earnings management, using tax rates as a moderating variable, among LQ45 index companies on the Indonesian Stock Exchange (BEI) from 2017-2019. Using a quantitative descriptive method and Smart PLS 3 software for analysis, the study found that tax planning significantly influences earnings management, while deferred tax expense does not. Tax rates moderate the impact of tax planning but not deferred tax expense on earnings management. These results emphasize the role of tax planning in earnings management and suggest that tax rates should be considered in regulatory policies. Future research should explore additional variables like company age and size. Highlight: Tax planning significantly influences earnings management. Tax rates moderate tax planning's effect on earnings management. Deferred tax expense has no direct impact on earnings management. Keyword: Earnings management, tax planning, deferred tax expense, tax rates, Indonesian Stock Exchange